The effects of the temperature in the testing system on the measurements of thermal rock strain with clip-on extensometers. (January 2022) - Pei, L.; Blöcher, G.; Wang, Y.J.; Milsch, H.; Zimmermann, G.; Huenges, E.; Xiang, W.
Highlights: Heterogeneous temperature distributed in the testing system. Plug-in temperature yielded the apparent irreversible amplification. Apparent amplification resulted in the apparent residual sample strain. Abstract: The present work was aimed to identify and quantify the offsets biasing the thermal rock strain as measured with clip-on extensometers at a mechanical testing system (MTS) so as to increase the reliability of such measured strain. We conducted an experiment via cycling the temperature of a sample of aluminum alloy between ambient temperature and 90 °C under the hydrostatic confining pressure as maintained at 2 MPa. Thereby, the readouts of the extensometers appeared to be irreversible subsequent to the temperature cycle mimicking residual deformation in the sample. The numerically simulated temperature in the setup of the testing system was heterogeneous throughout such temperature cycling test showing an irreversible plug-in temperature in particular. These temperatures resulted in the apparent amplification of the circuit as constituted by the extensometer and the amplifiers as well as the relevant reading offset. Such induced offset biased the actual sample strain besides the expansion (contraction) in the metal parts of the extensometers yielding the apparent irreversible strain in the sample. We presented a workflow for quantifying the amplification- and the metal part-related offsets. The validity of the workflow was demonstrated via rectifying the strain in a rock sample that was monitored throughout a temperature cycle between 30 °C and 40 °C. Our present work would be referable for experimental researches on thermal rock strain with similar setup of measurement. The amplification- and the metal part-related offsets could be likewise estimated and excluded from the measurements conducted elsewhere before the strain in a tested sample could be obtained.